Etika Islam sebagai Fondasi dalam Pembangunan Ekonomi Inklusif dan Berkeadilan - Sumarta, Sumarta; Budiyanto, Tenda (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2025)
Islamic ethics play a crucial role as a foundation for inclusive and just economic development. Concepts such as justice, honesty, and balance in Islamic teachings form the basis for economic principles that prioritize social interests and fair distribution. This research examines how Islamic ethical principles can be implemented in the context of modern economic development to create social inclusion and justice. The study uses a qualitative approach to delve into the understanding of the foundations of inclusive and just economic development based on Islamic ethical principles. Through theoretical analysis and case studies, the research shows that the application of Islamic ethics in economic policy can enhance accessibility, equality, and community participation in the economic process. Islamic ethics provide a holistic and sustainable perspective on economic development. The principle of justice in Islam encompasses not only equality of opportunity but also emphasizes fair distribution of wealth and economic outcomes. Community empowerment is emphasized as a means to ensure active participation in economic decision-making and equitable distribution of economic benefits. Additionally, the concept of social responsibility and the harmony between spirituality and materialism offer a comprehensive view of the relationship between humans, the environment, and the economy. Keywords: Islamic Ethics, Economic Development, Social Inclusion, Justice, Economic Principles